The relationship between cuticular lipids and associated gene expression in above ground organs of Thellungiella salsugineum (Pall.) Al-Shehbaz & Warwick. (October 2019) - Xu, Xiaojing; Xue, Kun; Tang, Shuai; He, Junqing; Song, Buerbatu; Zhou, Minqi; Zou, Yanli; Zhou, Yijun; Jenks, Matthew A.
Highlights: Cuticle morphology was viewed by SEM of five organs of Thellungiella . Cuticular lipids (wax and cutin) composition was determined in Thellungiella . Cuticle-associated genes expression was performed by transcriptome sequencing. Relationship between cuticle and adaptation to extreme environments was discussed. Abstract: The cuticle plays a critical role as barrier between plant and environment. Here, cuticular wax morphology, cuticular wax and cutin monomer composition, and expression of associated genes in five above ground organs were examined in model extremophyte Thellungiella salsugineum . Alkanes, ketones, and 2-alcohols were the predominant wax constitutes in rosette leaves, inflorescence stem leaves, stems, and siliques, whereas alkanes and acids were the predominant cuticular lipids in whole flowers. Unsubstituted acids were the most abundant cutin monomers in vegetative organs, especially C18:2 dioic acids, which reached the highest levels in stems. Hydroxy fatty acids were the predominant cutin monomers in flowers, especially 16−OH C16:0 and diOH C16:0. High-throughput RNA-Seq analysis using the Hiseq4000 platform was performed on these five above organs of T. salsugineum, and the differentially expressed lipid-associated genes and their associated metabolic pathways were identified. Expression of genes associated in previous reports to cuticle production, including those having roles in cuticle lipid biosynthesis, transport, and regulation were examined. The association of cuticle lipid composition and gene expression within different organs of T. salsugineum, and potential relationships between T. salsugineum 's extreme cuticle and its adaptation to extreme environments is discussed.